Rice pest repellent device (bird) using Telegram based on Internet of Things - SHERLY; Oriza Candra (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This research is aimed at designing a rice pest repellent device using IoT (Internet of Things) based telegrams, the purpose of this design is to improve monitoring and security of rice in the fields in an effort to minimize crop losses caused by rice pests in the form of sparrows and bondol. The tool designed will collect information data continuously from sensors installed around the rice through Internet of Things connectivity and the data can be accessed via telegram on the user's smartphone. With the ESP32 Devkit which acts as the brain of the programming and will move the cans around the rice fields connected to the rope by the servo motor if there is a movement detected by the PIR sensor, a notification will be sent to the telegram on the smartphone. It is hoped that there will be an increase in the efficiency of monitoring and security of rice plants in the fields with the implementation of the rice pest repellent device designer using IoT (Internet of Things) based telegrams